Modulatory Nano/Micro Effects of Diabetes Development on Pharmacology of Primary and Secondary Bile Acids Concentrations - Mooranian, Armin; Zamani, Nassim; Takechi, Ryu; Luna, Giuseppe; Mikov, Momir; Goločorbin-Kon, Svetlana; Kovacevic, Bozica; Arfuso, Frank; Al-Salami, Hani (Current Diabetes Reviews, 2020)
Background: Recent studies have suggested that hyperglycaemia influences the bile acid profile and concentrations of secondary bile acids in the gut. Introduction: This study aimed to measure changes in the bile acid profile in the gut, tissues, and faeces in type 1 Diabetes (T1D) and Type 2 Diabetes (T2D). Methods: T1D and T2D were established in a mouse model. Twenty-one seven-weeks old balb/c mice were randomly divided into three equal groups, healthy, T1D and T2D. Blood, tissue, urine and faeces samples were collected for bile acid measurements. Results: Compared with healthy mice, T1D and T2D mice showed lower levels of the primary bile acid, chenodeoxycholic acid, in the plasma, intestine, and brain, and higher levels of the secondary bile acid, lithocholic acid, in the plasma and pancreas. Levels of the bile acid ursodeoxycholic acid were undetected in healthy mice but were found to be elevated in T1D and T2D mice. Conclusion: Bile acid profiles in other organs were variably influenced by T1D and T2D development, which suggests similarity in effects of T1D and T2D on the bile acid profile, but these effects were not always consistent among all organs, possibly since feedback mechanisms controlling enterohepatic recirculation and bile acid profiles and biotransformation are different in T1D and T2D.
Keywords: balb/c mice